Effectiveness of Local Government Led School Management in Boosting Enrolment Rates: Evidence from Nepal (Prithvi Academic Journal, 2025)
Local government-led school management has emerged as a transformative approach to enhance access, equity, and efficiency in education. In Nepal, decentralization reforms have sought to improve enrollment rates and gender equity, but their long-term effectiveness and challenges have received limited scholarly attention. This study evaluates the impact of local governance on enrollment trends using a mixed-methods approach, analyzing quantitative data from World Bank Indicator (1999–2023) and contextualizing findings with qualitative insights. Fully Modified Ordinary Least Squares (FMOLS) regression was employed to examine long-run relationships and structural changes. The results reveal a significant post- 2017 boost in primary enrollment rates, driven by decentralization reforms, but also indicate a declining growth rate in enrollment thereafter. Regarding the key variables, Net Enrollment Rates (NER), Gross Enrollment Rates (GER), and Gender Parity Index (GPI) demonstrate progress, with GPI achieving parity in primary education by 2012. However, challenges persist, including disparities in secondary education, a decline in secondary GPI, and increasing reliance on private schooling, which raises equity concerns. The FMOLS findings underscore the transformative potential of decentralization while highlighting systemic gaps in retention, public school competitiveness, and regional equity. Strengthening local leadership, addressing socio-economic barriers, and reducing disparities are essential to sustain progress. Nepal’s experience demonstrates that while local government-led reforms can ignite progress, targeted interventions are critical to ensuring inclusive and equitable educational outcomes.